Formulation and Optimization of Sodium Alginate Polymer Film as a Buccal Mucoadhesive Drug Delivery System Containing Cetirizine Dihydrochloride - Krisztián Pamlényi; Katalin Kristó; Orsolya Jójárt-Laczkovich; Géza Regdon (MDPI AG, 2021)
Currently, pharmaceutical companies are working on innovative methods, processes and products. Oral mucoadhesive systems, such as tablets, gels, and polymer films, are among these possible products. Oral mucoadhesive systems possess many advantages, including the possibility to be applied in swallowing problems. The present study focused on formulating buccal mucoadhesive polymer films and investigating the physical and physical-chemical properties of films. Sodium alginate (SA) and hydroxypropyl methylcellulose (HPMC) were used as film-forming agents, glycerol (GLY) was added as a plasticizer, and cetirizine dihydrochloride (CTZ) was used as an active pharmaceutical ingredient (API). The polymer films were prepared at room temperature with the solvent casting method by mixed two-level and three-level factorial designs. The thickness, tensile strength (hardness), mucoadhesivity, surface free energy (SFE), FTIR, and Raman spectra, as well as the dissolution of the prepared films, were investigated. The investigations showed that GLY can reduce the mucoadhesivity of films, and CTZ can increase the tensile strength of films. The distribution of CTZ proved to be homogeneous in the films. The API could dissolve completely from all the films. We can conclude that polymer films with 1% and 3% GLY concentrations are appropriate to be formulated for application on the buccal mucosa as a drug delivery system.